2008
DOI: 10.1108/17542730810881366
|View full text |Cite
|
Sign up to set email alerts
|

Affective design of waiting areas in primary healthcare

Abstract: Purpose -This paper seeks to deal with affective design of waiting areas (servicescapes) and has twofold aims. The first, is to explore affective values for waiting areas. The second, is to identify interactions between physical design attributes and affective values. Design/methodology/approach -This study included a free association method for data collection, applying Kansei engineering methodology to extract design solutions relating to specific feelings. The study was undertaken at six primary health cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2009
2009
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Furthermore, in a study conducted by Arneill and Devlin (2002), 47 college students and 58 citizens evaluated the 35 slides of physicians’ waiting rooms and found that perceived quality of care and level of comfort were highly significant for well-lit, nicely furnished waiting areas with artwork as compared to poorly lit waiting areas with outdated furnishings and no artwork. Ayas and colleagues (2008) conducted interviews with 88 patients and staff in six primary health centers in Sweden and found that the seating arrangements in the waiting areas along with other design attributes including lighting, color, privacy, and green plants contributed to creating positive affective values such as a feeling of calmness in the waiting areas.…”
mentioning
confidence: 99%
“…Furthermore, in a study conducted by Arneill and Devlin (2002), 47 college students and 58 citizens evaluated the 35 slides of physicians’ waiting rooms and found that perceived quality of care and level of comfort were highly significant for well-lit, nicely furnished waiting areas with artwork as compared to poorly lit waiting areas with outdated furnishings and no artwork. Ayas and colleagues (2008) conducted interviews with 88 patients and staff in six primary health centers in Sweden and found that the seating arrangements in the waiting areas along with other design attributes including lighting, color, privacy, and green plants contributed to creating positive affective values such as a feeling of calmness in the waiting areas.…”
mentioning
confidence: 99%
“…These authors leveraged attention theory in a servicescape framework and empirically demonstrated that home-like cancer treatment centers enabled the patients to relieve their cancer-related fatigues which eventually aided them in a better restoration process. Another study conducted by Ayas et al (2008) explored the affective qualities of healthscape in primary healthcare units' waiting areas. Data collected from a sample of patients in Sweden revealed that core design attributes like lighting, sound level, and seating arrangements of waiting areas created a feeling of calmness among patients.…”
mentioning
confidence: 99%
“…By improving physical environmental dimensions of a healthcare facility (air quality, acoustics, lighting, seating arrangements, etc. ), significant effects on staff health and work efficiency could be gained (Ulrich et al 2004;Ayas, Eklund, and Ishihara 2008;Salonen et al 2013). A well-designed hospital increases users' well-being, satisfaction, patient safety, expedites patient recovery rates, makes the space efficient, effective, productive, user friendly and comfortable, while reducing medical errors, hospital acquired infections, staff stress and injuries (Ulrich 1999;Gesler et al 2004;Gluck 2007;Ulrich et al 2008;Poldma 2009;Rechel, Buchan, and McKee 2009;Haron, Hamid, and Talib 2012;Mourshed and Zhao 2012).…”
Section: Introductionmentioning
confidence: 97%
“…Good hospital design can also enhance hospital ergonomics by making the facility more affective and appealing to patients and other visitors (Ayas, Eklund, and Ishihara 2008). For instance, making sure hospital users' have enough privacy, colours, child play areas and green plants in hospital waiting areas has been shown to instil a feeling of calmness among them (Ayas, Eklund, and Ishihara 2008). Hignett and Lu (2009) have identified a need for ergonomic designers to produce evidence to support safer working practices relating to spatial requirements.…”
mentioning
confidence: 98%
See 1 more Smart Citation